The university is closed for open day : themes and scenes from 21st century Australia - Knight, Stephen (Melbourne University Press, 2019)
Where is analysis in this age of banal tweets and narcissistic comments? Stephen Knight turns his modernly analytical and historically aware mind to current attitudes and actions in need of serious examination. What is the impact of the bush myth on the national consciousness of Australian fiction? What of the modern shift in writing about Indigenous issues, from white writers to First Peoples? What has suddenly happened to Australian crime fiction?Other essays look at unravelling travelling, the tiny machines that obsess us, then those bizarrely flourishing modern identity-enhancers--tattoos and personalised number plates--and of course, the state of the contemporary university. Here is 21st century national complexity, its origins and its international connections, explored in a socially referential and almost always serious way.